Case report: Non-thrombotic iliac vein lesion: an unusual cause of unilateral leg swelling in a patient with endometrial carcinoma - Zeman, Jan; Kompella, Ritika; Lee, JuYong; Kim, Agnes S. (Frontiers in Cardiovascular Medicine, 2023)
81-year-old female presented with subacute right lower extremity edema found to be caused by iliac vein compression secondary to an enlarged external iliac lymph node later to be identified as relapsed newly metastatic endometrial carcinoma. Patient underwent full iliac vein lesion and cancer work-up and an intravenous stent was placed.